TESTING OF TWO‐STAGE CULTIVATION OF DUNALIELLA SALINA TEOD. (TEODORESCO, 1905) IN THE SEVASTOPOL REGION - I. N. Gudvilovich; A. B. Borovkov (Юг России: экология, развитие, 2019)
Aim. In this work, we set out to study the effect of surface irradiance on the growth rate and the pigment ratio of D. salina, as well as to test a technology for semi‐industrial cultiva‐ tion of D. salina aimed at obtaining its biomass enriched with β‐carotene.Methods. D. salina was cultivated under semi‐industrial conditions in a greenhouse module of the A. O. Kovalevsky Institute of Marine Biological Research. Square tanks (1 × 1 m) lined with polyethylene film and laid on a flat ground surface were used as propagators. The culture layer had a thickness of 10 cm and a volume of 100 litres. Pre‐grown D. salina was diluted using fresh medium without salts – sources of nitrogen and phosphorus. Dunaliella was cultivated under natural light with continuous stirring.Results. We determined the range of surface irradiance, which can be considered optimal for intensive cultivation of D. salina in terms of energy and mineral costs. Across this range, the average growth rate of the culture under experimental conditions amounted to 0.23–0.27 g DW/(l∙day), whereas the ratio of Car / Chl a increased by a factor of 1.5‐ 2, which indicates changes in the pigment composition of D. salina. It is experimentally shown that the content of carotenoids in the tanks increased by 1.3 times amounting to 600 mg per 1 m2 at a Car/Chl a ratio of 4.5 at the second stage of D. salina cultivation.Conclusions. Carotenoid accumulation during semi‐industrial cultivation of D. salina occures due to two factors: in‐ creased natural irradiance and temperature without an additional increase in salinity and blowing of carbon dioxide, which reduces the costs of its industrial cultivation. This two‐stage cultivation method can be used to develop a technology for obtaining Dunaliella biomass enriched with β‐carotene in the southern regions of the Russian Federation.